Learning of second language sound contrasts: Effects of training on the perception and production of second language vowel and consonant duration - Saloranta, Antti (fi=Turun yliopisto|en=University of Turku|, 2022)
Listen-and-repeat training has been shown to be an effective tool for the learning of non-native phoneme contrasts. The aim of this thesis was to examine the learning of non-native duration contrasts using short-term listen-and-repeat training with adult learners. Learning results were examined with event-related potentials, behavioral discrimination and identification tasks, and production tasks. In addition, the learning of non-native vowel duration in a classroom setting was investigated. Study I focused on listen-and-repeat training with articulation instructions in the learning of a non-native vowel quality contrast. The results showed that the participants were able to adjust their production of the contrast after only one training session. In Studies II and III, participants underwent two days of training with a nonnative vowel duration contrast, and their performance was measured on trained, untrained and non-linguistic duration contrasts. Study II used behavioral discrimination and production tasks, and Study III additionally used the electric event-related potentials MMN and N1. Study II showed tentative training-related improvements in the discrimination and production of the trained contrast. Study III found increased MMN amplitudes, decreased N1 latencies and improved behavioral discrimination performance for the trained stimuli. Changes to general detection of acoustic duration contrasts were also seen in the elicitation of an N1 response for the untrained contrast. No training-related changes in production were observed. Study IV used a two-day training paradigm on stop and sibilant duration contrasts, measuring learning results with MMN, behavioral discrimination and a production task. No training-related improvement was observed, but a clear difference emerged between the consonant types, with sibilants proving less difficult for the participants than stops. Study V examined the learning of non-native vowel duration contrasts on an intensive language course. Similarly to the listen-and-repeat studies, perceptual identification performance improved, but no improvement was observed in production. Overall, these results suggested that perception of non-native vowel duration contrasts can be improved fairly quickly, and they are learned more easily than production. More research is needed regarding the learning of consonant duration.

Vieraan kielen äänne-erojen oppiminen: Harjoittelun vaikutus vieraan kielen vokaali- ja konsonanttikestoerojen havaitsemiseen ja tuottoon Kuuntele ja toista –harjoittelun on osoitettu olevan tehokasta vieraan kielen äänneerojen oppimisessa. Tämän opinnäytetyön tavoitteena oli tutkia vieraan kielen kestoerojen oppimista aikuisilla oppijoilla lyhyen kuuntele ja toista –harjoittelun avulla. Oppimistuloksia mitattiin herätevasteilla, behavioraalisilla erottelu- ja identifikaatiokokeilla, sekä tuottokokeilla. Lisäksi tutkittiin vieraan kielen vokaalikestoerojen oppimista luokkahuoneessa. Osatutkimus I tutki artikulaatio-ohjeilla tuettua kuuntele ja toista –harjoittelua vieraan kielen vokaalilaatueron oppimisessa. Tulokset osoittivat, että osallistujat pystyivät muokkaamaan tuottoaan jo yhden harjoituskerran jälkeen. Osatutkimuksissa II ja III käytettiin kahden päivän kuuntele ja toista –harjoitusta vieraan kielen vokaalikeston oppimiseen. Oppimista mitattiin harjoitellulla, harjoittelemattomalla ja ei-kielellisellä kestoerolla. Osatutkimuksessa II käytettiin behavioraalista erottelua ja tuottokoetta, ja osatutkimuksessa III lisäksi MMN- ja N1-herätevasteita. Osatutkimuksessa II todettiin alustavia parannuksia harjoitellun eron havaitsemisessa ja tuotossa. Osatutkimuksessa III havaittiin harjoitellulla erolla kasvanut MMN-amplitudi, laskenut N1-vasteen latenssi sekä parantunut behavioraalinen erottelukyky. N1-vasteen elisitoituminen harjoittelemattomalle erolle viittasi myös yleisen akustisen erottelukyvyn paranemiseen. Tuoton suhteen muutoksia ei havaittu. Osatutkimuksessa IV käytettiin kaksipäiväistä harjoittelua vieraan kielen klusiili- ja sibilanttikestoerojen harjoitteluun. Oppimista mitattiin MMN:n, erottelukokeen sekä tuottokokeen avulla. Harjoittelu ei parantanut konsonanttien havaitsemista eikä tuottoa, mutta konsonanttien välillä havaittiin selkeä ero, jonka perusteella sibilantit olivat koehenkilöille helpompia kuin klusiilit. Osatutkimus V tarkasteli vieraan kielen vokaalikestoerojen oppimista intensiivisellä kielikurssilla. Kuten aiemmissa osatutkimuksissa, behavioraalinen havaitseminen kehittyi, mutta tuotossa ei havaittu parannusta. Kokonaisuudessaan tutkimukset viittasivat siihen, että vieraan kielen vokaalikestoerojen havaitsemista voidaan parantaa suhteellisen nopeasti harjoittelulla, ja se kehittyy helpommin kuin kestoerojen tuotto. Konsonanttien keston oppimisen suhteen tarvitaan jatkotutkimusta.